2019
DOI: 10.3389/fmicb.2019.01267
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Tungsten-Microbial Interface of the Metal Immobilizing Thermoacidophilic Archaeon Metallosphaera sedula Cultivated With Tungsten Polyoxometalate

Abstract: Inorganic systems based upon polyoxometalate (POM) clusters provide an experimental approach to develop artificial life. These artificial symmetric anionic macromolecules with oxidometalate polyhedra as building blocks were shown to be well suited as inorganic frameworks for complex self-assembling and organizing systems with emergent properties. Analogously to mineral cells based on iron sulfides, POMs are considered as inorganic cells in facilitating prelife chemical processes and displaying “life-like” char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 68 publications
4
13
0
Order By: Relevance
“…Apparently, only certain cell wallmetal interactions can strengthen prokaryotic cell envelopes and augment their structural stability implicating in cell preservation during harsh long-term dehydration. In this regard, the tungsten incorporation by the cell envelope of M. sedula (Blazevic et al, 2019;Milojevic et al, 2019a) may certainly serve as an efficient strengthening strategy, as this is a hard element with the highest melting point and extraordinary properties among all metals. Being suitable for high-temperature applications in energy and lighting technology, and in the space industry, it is also used as alloys, superalloys, and radiation-shielding.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Apparently, only certain cell wallmetal interactions can strengthen prokaryotic cell envelopes and augment their structural stability implicating in cell preservation during harsh long-term dehydration. In this regard, the tungsten incorporation by the cell envelope of M. sedula (Blazevic et al, 2019;Milojevic et al, 2019a) may certainly serve as an efficient strengthening strategy, as this is a hard element with the highest melting point and extraordinary properties among all metals. Being suitable for high-temperature applications in energy and lighting technology, and in the space industry, it is also used as alloys, superalloys, and radiation-shielding.…”
Section: Discussionmentioning
confidence: 99%
“…Being suitable for high-temperature applications in energy and lighting technology, and in the space industry, it is also used as alloys, superalloys, and radiation-shielding. We have previously reported that M. sedula (cultivated on scheelite and W-POM) mineralizes its S-layer via encrusting with crystalline nanoparticles containing tungsten carbide-like structures (Blazevic et al, 2019;Milojevic et al, 2019a). Tungsten exhibits a hardness of ∼9-9.5 on the Mohs hardness scale (Tabor, 1954) and can potentially provide an efficient barrier against water loss, warranting preservation of cell integrity after desiccation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations